2015
DOI: 10.1007/s11064-015-1621-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Chronic Methamphetamine Administration and Withdrawal in Mice with Relaxin-3/RXFP3 Deficiency

Abstract: Methamphetamine (METH) is a highly addictive psychostimulant, and cessation of use is associated with reduced monoamine signalling, and increased anxiety/depressive states. Neurons expressing the neuropeptide, relaxin-3 (RLN3), and its cognate receptor, RXFP3, constitute a putative 'ascending arousal system', which shares neuroanatomical and functional similarities with serotonin (5-HT)/dorsal raphe and noradrenaline (NA)/locus coeruleus monoamine systems. In light of possible synergistic roles of RLN3 and 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…Overall, these results are consistent with a recent study suggesting a depressivelike state rather than an anxiety-like state during METH-early withdrawal using a rat self-administration model [32]. Moreover, Haidar et al [33] showed that female C57BL6 mice subjected to chronic METH regimen exhibited behavioral despair during the first 48 h of withdrawal without evident anhedonic-like (SPT) and anxiety-like behaviors (measured by SPT and EPM, respectively). The lack of alterations during the performance of the open field and pole test indicates that the METH-exposed animals have normal motor function; thus, ruling out that putative motor deficits may be responsible for the observed depressive-like behavior.…”
Section: Resultssupporting
confidence: 91%
“…Overall, these results are consistent with a recent study suggesting a depressivelike state rather than an anxiety-like state during METH-early withdrawal using a rat self-administration model [32]. Moreover, Haidar et al [33] showed that female C57BL6 mice subjected to chronic METH regimen exhibited behavioral despair during the first 48 h of withdrawal without evident anhedonic-like (SPT) and anxiety-like behaviors (measured by SPT and EPM, respectively). The lack of alterations during the performance of the open field and pole test indicates that the METH-exposed animals have normal motor function; thus, ruling out that putative motor deficits may be responsible for the observed depressive-like behavior.…”
Section: Resultssupporting
confidence: 91%
“…Adolescent METH exposure can induce emotional, behavioral, and cognitive deficits, but not all the deficits last for a long time (Hayase et al, 2005; McGregor et al, 2005; Haidar et al, 2016; Fonseca et al, 2017; Thompson et al, 2017). Based on our results, adolescent METH exposure-induced working memory deficits in the Y-maze spontaneous alternation test and anxiety-like behavior in the EPM test spontaneously recovered after long-term METH abstinence; reduced novel spatial exploration was observed both in adolescence and subsequent adulthood; and mild hyperactivity and impaired social recognition memory were found only in subsequent adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, effects of chronic Meth pretreatment on anxiety have been variable. For example, a 10-day escalating dose protocol in mice induced no changes in anxiety measures in the EPM or light/dark box (48) while studies in rats showed increased anxiety or no change in the EPM depending on the age or extent of Meth exposure or time following exposure (4951). These results suggest that dosing and testing protocol are very important for long-term effects of Meth on behavior.…”
Section: Discussionmentioning
confidence: 99%